Pengaruh Kualitas Pelayanan Dan Manajemen Hubungan Pelanggan Terhadap Loyalitas Mahasiswa Kampus Pusat Institut Stiami Jakarta - Sholeh, Muhammad (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2021)
The purpose of this study was to determine the significance of the effect of service quality and customer relationship management on student loyalty STIAMI. This research is a quantitative study with a sampling technique in the form of simple random sampling totaling 97 students. The results showed that there was no significant influence given service quality to student loyalty, but customer relationship management had a significant effect on student loyalty. In addition, simultaneously service quality and customer relationship management have a significant influence on student loyalty by 44.1%